Integrity and Performance of High School Teachers in Pekanbaru - Isjoni Isjoni; Afrianto Daud; Azhar Azhar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This study was aimed at finding if integrity affects the performance of High School Teachers in Pekanbaru. So the hypothesis of this study is that if the integrity has an influence on the performance of high school teachers in Pekanbaru. The method used in this study was a survey with correlational techniques. This technique was carried out to analyze the influence of two independent variables X with dependent variables Y. The population in this study were all high school teachers (178 teachers) and the samples were teachers who had received teacher certification at the SMAN Kecamatan 121 Tenayan Raya. Data were analysed using descriptive analysis techniques and inferential analysis to test hypotheses. The requirements for analyzing the data are: normality test, homogeneity test, and linearity test. The results showed that integrity had a significant effect with a positive direction on teacher performance in the Tenayan Raya High School in Pekanbaru. This is indicated by the regression coefficient of integrity against teacher performance of 0.083. The point is that if the integrity variable rises by one unit, an increase in teacher performance is 0.083. Furthermore, the effect of the variable integrity on teacher performance resulted in a value of 0.69%. This means that integrity contributes significantly to teacher performance by 0.69%. This contribution is in the very low category. Therefore, it can be concluded that integrity has a positive and significant effect on teachers’ performance in Tenayan Raya High School.